A modified die and tool set for material testing in the industry - Baharudin, Nur Sara Syuhada; Mohd Tahir, Suraya; Mohd Yusoff, Syamimi; Anuar, Anuar (Taylor and Francis, 2022)
In powder compaction process, one of the most essential aspect that needs to be considered is the strength of the compacted materials that is commonly measured using the fracture toughness test. In order to conduct the fracture toughness test, a notch needs to be created on the sample. This is usually done through machining the sample. A recent patented work has been able to produce a modified die and tool set that can create a notch in the compacted sample without the need of subsequent machining of the sample. However, there is a research gap, where the potential utilisation of this novel modified die and tool set by the relevant industrial players, has not been conducted. Therefore, the objective of this work is to conduct a market analysis to determine the manufacturing sectors or organisations that can utilise this modified die and tool for their material testing. A survey was conducted on various industries including pharmaceuticals, cosmetics, medical device, food, electrical/electronic, hardware, construction, and automotive. From the survey results, the automotive sector showed the most potential. In conclusion, all responded companies favoured to manufacture the modified die and tool set themselves instead of purchasing the patent only.